Hubungan Perhatian Orang Tua terhadap Kesiapan Belajar Siswa dan Prestasi Belajar - Putri Oktavia Wulan Sari (Pedagogi: Jurnal Ilmu Pendidikan, 2018)
Readiness learning is the most important factor in determining successful students in learning and receiving learning. Learning will enable the individual to make changes within himself. This change can be a mastery of a certain skill, a change of attitude, have a different science than before a person doing the learning process. The teaching of learning is closely related to the motivation to learn in the achievement of student achievement in school. Parents are the main responsible person in the education of children. Parents who determine the future of the child. But recognize the limitations and opportunities they have, so parents ask other outsiders to help educate their children. Others are teachers, relatives, even grandmothers at school and at home. Parents play an important role in determining the success of their children's education. They have important responsibilities and roles for children, among others, can be realized by guiding the continuity of children's home study in accordance with the programs that have been learned by children in school. Parental concern can be done by supervising and guiding the child's schoolwork and helping to solve the child's problem in learning.